CORAK SOSIALISME PESANTREN - Husnul Amin (Jurnal Pendidikan Islam, 2012)
This writing is to elaborate the idea of reconstructing system of Pesantren. This is due to the demand of real social needs and competition on the quality among educational institutions. As a result, reconstructing education system of Pesantren is a must in order to prepare Pesantren to be modern educational Institutions that are ready to compete with other educational institutions. Therefore, Pesantren needs one comprehensive education system that makes it function as a transmission either in form of formal or non-formal education. As the impact, Pesantren can actualize the essence of human life that is always involved in various changes in times since the dynamics of Pesantren in the future cannot be separated from the process of globalization. In this case, the existence of both traditional and modern Pesantren in the future will be determined by its ability to integrate culturally with the international system characterized by a more rational, dynamic and competitive relationship system.